Microbial analysis and heavy metal determination of janitor fish (Pterygoplichthys spp.) in Marikina River, Philippines - Santos, Ma. Jiezl C.; Dognidon, Kenneth Andrew R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
Microbial analysis and heavy metal determination was done for raw and cooked Janitor fish (Pterygoplichthys spp.) to assess its safety for human consumption. Raw, boiled and grilled janitor fish was analyzed for total plate count, total coliform count, total E.coli count, presence of Salmonella spp., and presence of Vibrio spp.The fishes were also analyzed for Cadmium, Lead and Iron content. Results revealed that cadmium and lead were not detected in the raw, boiled, grilled janitor fish. Fe concentrations of all the samples are within the standard limit by FAO/WHO (2011), which is 43mg/kg. Raw janitor fish has 33.05 ± 9.83 mg/kg while boiled and grilled has 17.35 ± 16.90 mg/kg and 20.95 ± 14.85 mg/kg, respectively. Raw janitor fish has the highest total plate count which is 5.00 log CFU/g but was still within the standard limit of 5.70 log CFU/g. On the other hand, boiled janitor fish has the lowest total plate count with 3.23 logCFU/g. For the total coliform and total E.coli count, raw janitor fish was the highest having 5.00 log CFU/g and 3.80 log CFU/g, respectively. This exceeded the standard limit for TCC and TEC which is 2 log CFU/g and 1.04 log CFU/g, respectively. Meanwhile, boiled janitor fish has the lowest count for both TCC and TEC with <2 logCFU/g. Moreover, all the samples were determined to be present for Salmonella spp.and absent for Vibrio spp.
Thesis Classification: C
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Pterygoplichthys -- Philippines -- Marikina; Fishes -- Philippines -- Marikina; Fishes -- Microbiology -- Philippines -- Marikina